Akt‐mediated foxo1 inhibition is required for liver regeneration. Issue 5 (18th December 2015) - Pauta, Montse; Rotllan, Noemi; Fernández‐Hernando, Ana; Langhi, Cedric; Ribera, Jordi; Lu, Mingjian; Boix, Loreto; Bruix, Jordi; Jimenez, Wladimiro; Suárez, Yajaira; Ford, David A.; Baldán, Angel; et al.
Abstract : Understanding the hepatic regenerative process has clinical interest as the effectiveness of many treatments for chronic liver diseases is conditioned by efficient liver regeneration. Experimental evidence points to the need for a temporal coordination between cytokines, growth factors, and metabolic signaling pathways to enable successful liver regeneration. One intracellular mediator that acts as a signal integration node for these processes is the serine‐threonine kinase Akt/protein kinase B (Akt). To investigate the contribution of Akt during hepatic regeneration, we performed partial hepatectomy in mice lacking Akt1, Akt2, or both isoforms. We found that absence of Akt1 or Akt2 does not influence liver regeneration after partial hepatectomy. However, hepatic‐specific Akt1 and Akt2 null mice show impaired liver regeneration and increased mortality. The major abnormal cellular events observed in total Akt‐deficient livers were a marked reduction in cell proliferation, cell hypertrophy, glycogenesis, and lipid droplet formation. Most importantly, liver‐specific deletion of FoxO1, a transcription factor regulated by Akt, rescued the hepatic regenerative capability in Akt1‐deficient and Akt2‐deficient mice and normalized the cellular events associated with liver regeneration. Conclusion: The Akt‐FoxO1 signaling pathway plays an essential role during liver regeneration. (Hepatology 2016;63:1660‐1674)